A 590 kb deletion caused by non‐allelic homologous recombination between two LINE‐1 elements in a patient with mesomelia‐synostosis syndrome. Issue 4 (22nd March 2017) - Kohmoto, Tomohiro; Naruto, Takuya; Watanabe, Miki; Fujita, Yuji; Ujiro, Sae; Okamoto, Nana; Horikawa, Hideaki; Masuda, Kiyoshi; Imoto, Issei
Abstract : Mesomelia‐synostoses syndrome (MSS) is a rare, autosomal‐dominant, syndromal osteochondrodysplasia characterized by mesomelic limb shortening, acral synostoses, and multiple congenital malformations due to a non‐recurrent deletion at 8q13 that always encompasses two coding‐genes, SULF1 and SLCO5A1 . To date, five unrelated patients have been reported worldwide, and MMS was previously proposed to not be a genomic disorder associated with deletions recurring from non‐allelic homologous recombination (NAHR) in at least two analyzed cases. We conducted targeted gene panel sequencing and subsequent array‐based copy number analysis in an 11‐year‐old undiagnosed Japanese female patient with multiple congenital anomalies that included mesomelic limb shortening and detected a novel 590 Kb deletion at 8q13 encompassing the same gene set as reported previously, resulting in the diagnosis of MSS. Breakpoint sequences of the deleted region in our case demonstrated the first LINE‐1s (L1s)‐mediated unequal NAHR event utilizing two distant L1 elements as homology substrates in this disease, which may represent a novel causative mechanism of the 8q13 deletion, expanding the range of mechanisms involved in the chromosomal rearrangements responsible for MSS.